Linguistic Factors and the Spelling Ability of Spanish Heritage Language Learners - Llombart-Huesca, Amàlia; Zyzik, Eve (Frontiers in Education, 2019)
Spelling is an aspect of literacy that causes significant difficulties for Spanish heritage language (HL) learners. Because little is known about how spelling skills are developed in this population, instructors of HL courses often struggle when attempting to teach spelling rules, leading to frustration among both teachers and students in heritage language courses. (Beaudrie, 2012). The current research study targets one of the most problematic areas of Spanish orthography: substitution of ‘s’ and ‘c’ letters to represent /s/. An experimental dictation task was designed in order to test two linguistic factors hypothesized to impact spelling accuracy: target letter (‘s’ vs. ‘c’) and cognate status of the word (cognate vs. non-cognate). Participants (n=72) were young adults, Spanish HL learners, who completed the dictation task in addition to a standardized measure of proficiency. The results indicate a main effect for cognate status (suggesting facilitative transfer from English), but no effect for letter. These results suggest that ‘s’ is not the default letter for representing /s/, contrary to what had been found in a number of previous studies. We discuss the data in the broader context of pedagogical proposals for targeting spelling among college-aged HL learners.